2019
DOI: 10.1021/acs.inorgchem.9b01917
|View full text |Cite
|
Sign up to set email alerts
|

Binary–Ternary Bi2S3–AgBiS2 Rod-to-Rod Transformation via Anisotropic Partial Cation Exchange Reaction

Abstract: Nanoscale chemical transformations based on partial cation exchange reactions are known as a componentincreased, shape-maintaining means for the design and tunable preparation of ternary or multinary metal chalcogenide compounds. Herein, we present a new material couple, Bi 2 S 3 −AgBiS 2 , to detail the binary−ternary chemical transformation via partial cation exchange and its reaction thermodynamics and kinetics. The preformed Bi 2 S 3 nanorods (NRs) act as both the reactant and the parent template, within w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 59 publications
(195 reference statements)
1
10
0
Order By: Relevance
“…As evident from the SEM image of the DES-synthesized AgBiS 2 sample (2 h of dwelling, phase pure by PXRD), AgBiS 2 particles possess a rod-like morphology, similar to that of Bi 2 S 3 (Figures and S4). The morphologies of AgBiS 2 and Bi 2 S 3 particles in this work are similar to those of AgBiS 2 nanorods that were made from pre-synthesized Bi 2 S 3 nanorods in oleylamine . However, Bi 2 S 3 synthesized in DES made of thioacetamide and choline chloride in an autoclave resulted in nanowire morphology …”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…As evident from the SEM image of the DES-synthesized AgBiS 2 sample (2 h of dwelling, phase pure by PXRD), AgBiS 2 particles possess a rod-like morphology, similar to that of Bi 2 S 3 (Figures and S4). The morphologies of AgBiS 2 and Bi 2 S 3 particles in this work are similar to those of AgBiS 2 nanorods that were made from pre-synthesized Bi 2 S 3 nanorods in oleylamine . However, Bi 2 S 3 synthesized in DES made of thioacetamide and choline chloride in an autoclave resulted in nanowire morphology …”
Section: Resultssupporting
confidence: 68%
“…The morphologies of AgBiS 2 and Bi 2 S 3 particles in this work are similar to those of AgBiS 2 nanorods that were made from pre-synthesized Bi 2 S 3 nanorods in oleylamine. 62 However, Bi 2 S 3 synthesized in DES made of thioacetamide and choline chloride in an autoclave resulted in nanowire morphology. 19 The optical properties of the synthesized AgBiS 2 and Cu 3 BiS were investigated using diffuse reflectance spectroscopy.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The transformation of one bismuth compound into another is mainly reported for oxides/oxyhalides and sulfides, 51−53 or in cation exchange cases. 54,55 To the best of our knowledge, this is the first experimental study of the mechanism in which a sulfide transforms into a sulfoiodide. The reaction medium under study is monoethylene glycol, which is a coordinating solvent and plays an important role in promoting the entrance of iodine atoms into the Bi 2 S 3 structure for the formation of BiSI.…”
Section: Introductionmentioning
confidence: 97%
“…The ionic radius of Ag + ion is 1.15 Å, which is quite favorable for the intercalation, and can initiate the CE process. Recently, Wang et al in their article have reported the conversion of Bi 2 S 3 to AgBiS 2 and highlighted the growth mechanism extensively . In our work, the Ag + -mediated CE has been done in a relatively low temperature (70 ° C) and via an intermediate heterostructure formation.…”
Section: Introductionmentioning
confidence: 88%
“…Recently, Wang et al in their article have reported the conversion of Bi 2 S 3 to AgBiS 2 and highlighted the growth mechanism extensively. 49 In our work, the Ag + -mediated CE has been done in a relatively low temperature (70 °C) and via an intermediate heterostructure formation. Interestingly, this intermediate heterostructure is found to be stable and exhibit a type-I band alignment.…”
Section: ■ Introductionmentioning
confidence: 99%